Assimilating to a boy's body shape for the sake of performance: three female athletes' body experiences in a sporting culture. Issue 2 (17th February 2017) - McMahon, Jenny; Barker-Ruchti, Natalie
Abstract : This paper explores three female swimmers' relationships with their male coaches and the body practices they were exposed to within Australian swimming. Particular attention is given to how the relationships and practices might relate to gender. Additionally, the article examines how (if at all) the conduct contributed to the social construction of an accepted female swimmer body. Through narrative accounts, the three adolescent female athletes articulate hierarchical male coach–female athlete relationships and specific body encounters they were exposed to and/or engaged with. Their experiences reveal how a sexually maturing body (growing breasts, female body shape and menstruating) was deemed unsuitable for performance and the swimmers were thus encouraged to transform their bodies and behaviours towards that of the boys. Using a feminist Foucauldian perspective, these accounts points to how the three swimmers came to regulate their diet, training and appearance in order to fulfil expectations. This self-regulation is problematic in two ways: first, no scientific evidence shows that a boy like physique is essential for best performance. Second, the stress from being pressured to achieve a particular body, as well as the shame that resulted from being unable to achieve the idealised physique, eventually caused the swimmers to develop an unhealthy relationship with their developing bodies. We highlight how those immersed in sporting contexts should recognise the serious implications of gender practices and power relations underpinning the male coach – female athlete dynamic in competitive sport.